On the structural and electronic properties of [Zn2(4,4'-bipyridine)(mes)4]n- (n=0-2), a homologous series of bimetallic complexes bridged by neutral, anionic, and dianionic 4,4'-bipyridine. - Irwin, M; Krämer, T; McGrady, J; Goicoechea, J (2011)
Addition of 1 equiv of potassium metal to a tetrahydrofuran (THF) solution of Zn(2)(4,4'-bipyridine)(mes)(4) (1; mes =2,4,6-Me(3)C(6)H(2)) in the presence of 18-crown-6 (1,4,7,10,13,16-hexaoxacyclooctadecane) yielded the radical anionic species [Zn(2)(4,4'-bipyridine)(mes)(4)](•-), which was characterized by single crystal X-ray diffraction in [K(18-crown-6)(THF)(2)][Zn(2)(4,4'-bipyridine)(mes)(4)] (2). A similar reaction employing 2 equiv of alkali metal afforded the related complex [K(18-crown-6)](2)[Zn(2)(4,4'-bipyridine)(mes)(4)] (3). The [Zn(2)(4,4'-bipyridine)(mes)(4)](n-) (n = 0-2) moieties present in 1-3 are largely isostructural, yet exhibit significant structural variations which arise because of differences in their electronic structure. These species represent a homologous series of complexes in which the ligand exists in three distinct oxidation states. Structural data, spectroscopic measurements, and density functional theory (DFT) calculations are consistent with the assignment of 1, 2, and 3 as complexes of the neutral, radical anionic, and dianionic 4,4'-bipyridyl ligand, respectively. To the best of our knowledge, species 2 and 3 are the first crystallographically characterized transition metal complexes of the 4,4'-bipyridyl radical and dianion.